Lactobacillus e Pediococcus de silagem, água, leite, soro fermento endógeno e queijo Minas artesanal da região de Campo das Vertentes: isolamento, identificação molecular e avaliações in vitro e in vivo do potencial probiótico - Felipe Machado de Santanna (2015)
Minas Gerais state is known for its famous artisanal cheese, made from raw milk and innoculated with endogenous starter culture named pingo. Due to its artisanal production, that cheese is rich in lactic acid bacteria (LAB), that may occur in different sources, such as environment, milk, starter cultures and also water. The aim of this study was to molecularly identify Lactobacillus spp. and Pediococcus spp. isolated from water, silage, milk, endogenous starter culture and Minas artisanal cheese fresh (0d) and rippened (7,14,21,28,and 60 days), from different dairy farms and identify its origin by stablishing phylogenetical relations between these samples, as well as evaluate its in vitro and in vivo probiotic potential. Ninety four Gram postive and catalase-negative samples were submitted to rRNA 16S-23S PCR reaction, and later thirty six being selected as belonging to Lactobacillus/Pediococcus group. The rRNA 16S sequencing showed five species: Lactobacillus plantarum, L. paracasei, L. brevis, L. rhamnosus and Pediococcus acidilactici. The rep-PCR (GTG)5 fingerprinting reaction allowed the montage of a dendrogram via UPGMA and showed Lactobacillus plantarum predominance amongst he other LAB (75,7%) from all the studies sources, followed by L. brevis (9,1%), L. paracasei (6,1%), P. acidilactici (6,1%) and L. rhamnosus (3,0%). These samples were then submitted to in vitro tests, being selected for its probiotic potential regarding biliar salts and acid (pH 2.0 and pH 1.5) resistance. A total of eight samples were selected by these tests, and then evaluated its antimicrobial susceptibility and pathogenic inhibition rate. Two samples (Lactobacillus plantarum LP4 and Pediococcus acidilactici PA2) showed best biliar salt and acid resistance, high pathogenic inhibition rate and low antibiotic resistance percentual and then were selected for in vivo evalution. The results of lethality and weight gain in mice orally infected with Salmonella entérica sorovar. Typhimurium and associated or not with oral administration of LP4 and PA2 showed low protective effect of bboth samples; although LP4 had showed hgher values of weight gain (p<0,05) in contrast of negative and positive (a comercial sample of L. casei) controls. These results indicates that L. plantarum LP4 sample showed satisactory in vitro values, as well as weight gain in orally infected S. Typhimurium mice, favoring future studies refering its use as a potential probiotic